2020
DOI: 10.1016/j.ahj.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Continuing versus suspending angiotensin-converting enzyme inhibitors and angiotensin receptor blockers: Impact on adverse outcomes in hospitalized patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)--The BRACE CORONA Trial

Abstract: Background Angiotensin-converting enzyme-2 (ACE2) expression may increase due to upregulation in patients using angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARBs). Because renin-angiotensin system blockers increase levels of ACE2, a protein that facilitates coronavirus entry into cells, there is concern that these drugs could increase the risk of developing a severe and fatal form of COVID-19. The impact of discontinuing ACEI and ARBs in patients with COVID-19 remains unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
120
1
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 33 publications
4
120
1
14
Order By: Relevance
“…Our study reported that chronic use of ACE-I/ARB is a protective factor for mechanical ventilation and associated with a lower mortality. A Randomized Clinical Trial comparing suspending or continuing use of ACE-I/ARB in chronic users is currently under way and should aid in understanding the role of those drugs among COVID-19 patients ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study reported that chronic use of ACE-I/ARB is a protective factor for mechanical ventilation and associated with a lower mortality. A Randomized Clinical Trial comparing suspending or continuing use of ACE-I/ARB in chronic users is currently under way and should aid in understanding the role of those drugs among COVID-19 patients ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised about the possible association between the use of RAAS inhibitors (mainly ACEIs and/or ARBs) with the risk of SARS‐CoV‐2 infection, the risk of severe COVID‐19 among those infected, or the risk of in‐hospital death among those with a positive test 4,5,6 . Several studies have concluded that there is no evidence of poor outcomes (increased severity or in‐hospital death) in patients infected with SARS‐CoV‐2 taking RAAS inhibitors 8,9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering hypertension, which is the most common comorbidity in middle‐aged and older adults (who suffer the greatest burden of fatal COVID‐19 cases), a possible beneficial/harm effect using some first‐line anti‐hypertensive medications such as angiotensin‐converting enzyme inhibitors (ACEIs) and/or angiotensin II receptor blockers (ARBs) has become controversial for the management of hypertensive patients in the current COVID‐19 pandemic period 4,5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection; yet there is lack of robust evidence supporting the use or discontinuation of RAAS medications. 2,3 Although, there is a theory that ACEi/ARBs antagonise RAAS which might reduce inflammation in COVID-19 pneumonia, thus reducing mortality. 2,4 The study by Zhang et al 4 reports the conclusion of a lower risk of all-cause mortality in the ACEi/ARBs group compared with the nonusers for hypertension.…”
mentioning
confidence: 99%